(untitled) (Architecture Image Studies, 2025)
Adapting a novel for the screen has elicited both positive and negative re-sponses in Indonesia. This paper aims to unpack the polemics of the film ad-aptation involving the authors, the audience, and the moviemakers. Consid-ering the various motives that filmmakers hold when adapting a novel, this article will investigate the reasons that influence moviemakers to make a film adaptation. Employing documentation studies, this qualitative study looks into online sources and scrutinizes the polemics surrounding film ad-aptation in Indonesia. With an emphasis on adaptation theory, this research investigates the discourses, challenges, and culture that underpin film adap-tation in the Indonesian context. The result of the study reveals that the In-donesian public has various views, both negative and positive, towards film adaptations. Meanwhile, the moviemakers should consider various factors, including profit, personal, religious, and historical preference, when making an adaptation.